Unveiling environmental identities: a mixed methods analysis of non-profit communication - Delvaux, Ibe; Van den Broeck, Wendy (Frontiers in Communication, 2024)
To address environmental issues, it is important to strengthen individuals' environmental self-identities. This research explored how environmental non-profit organizations (NPOs) use and perceive communication interventions (social norms, perceived environmental responsibility, and social comparison feedback) that could make the environmental social - and self-identities of their community salient. This is achieved by combining a quantitative content analysis of social media posts (n = 448), with six in depth-interviews with communication professionals working in NPOs. We found that descriptive social norms (25.7%) are the most frequently used intervention by NPOs. However, these norms can reduce personal responsibility for environmental actions, and NPOs rarely combine them with personal responsibility messages or injunctive norms, which could tackle this issue. Secondly, we found that the NPO communication professionals are implicitly focusing on increasing the group identification with the organization by using advocates and personal communication with their members. Furthermore, the included NPOs mainly communicate with individuals who already hold environmental values. Consequently, the study identifies a current mismatch between this environmentally conscious audience and the interventions the NPOs are utilizing. Descriptive social norms, which are widely used by the NPOs, are more appropriate for the general public-an audience with weaker connections to the NPOs but one they aim to reach more in the future. In contrast, injunctive and dynamic social norms, both minimally employed by the NPOs, appear more suitable for their current environmental audience. Last, we found that NPOs emphasize their responsibility in addressing environmental issues (20,8%) but neglect to acknowledge governmental efforts (0,9%), which could enhance citizens' environmental self-identity and promote pro-environmental behaviors. This study provides insight into more effective NPO communication strategies, particularly through better audience segmentation and integrating different types of social norms to enhance pro-environmental identities and behaviors.